2019
DOI: 10.20873/uft.2446-6492.2019v6n2p64
|View full text |Cite
|
Sign up to set email alerts
|

Reincidência Da Doença De Chagas No Brasil Por Vias Alternativas De Transmissão

Abstract: Este estudo tem como objetivo, identificar a incidência de casos notificados da doença de Chagas, assim como, elucidar a via de transmissão mais frequente no Brasil, destacar os fatores que corroboram com esta reincidência da doença e evidenciar se há necessidade de maiores investimentos em vigilância epidemiológica para a doença de Chagas no Brasil. Trata-se de um estudo epidemiológico, transversal e retrospectivo, onde foi realizada uma busca sistemática na literatura disponível em bancos de dados de relevân… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, it is observed that among the public control policies, the largest portion is directed to the control of transmission by vector or even to the transfusion route, with a lesser emphasis on the control of contaminated food, resulting in transmission of Chagas disease. orally (ARAUJO et al, 2019). However, this transmission route is still neglected in Brazil, which is an impasse in the face of reducing the incidence of this disease (SANTOS et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is observed that among the public control policies, the largest portion is directed to the control of transmission by vector or even to the transfusion route, with a lesser emphasis on the control of contaminated food, resulting in transmission of Chagas disease. orally (ARAUJO et al, 2019). However, this transmission route is still neglected in Brazil, which is an impasse in the face of reducing the incidence of this disease (SANTOS et al, 2021).…”
Section: Introductionmentioning
confidence: 99%